Artificial Intelligence and Ethics: Building an Artificial Intelligence System that Ensures Privacy and Social Justice - Muhammad Hermansyah; Ainun Najib; Any Farida; Rian Sacipto; Bagus Setya Rintyarna (GoAcademica Research & Publishing, 2023)
The term